Mahkamah Konstitusi dalam Sengketa Pilpres 2024: Lembaga Penegak Keadilan atau Arena Kepentingan Politik? - Mega Arinda Pramessella; Najwa Adhwa Ramadhani; Alifah Jasmine Kallista Remanu; Bella Ola Shakira; Achmad Aidil Viqri; Restu Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
The 2024 presidential election is the right moment for all Indonesians to participate in realizing the principles of democracy. However, in its implementation, there is a lot of public suspicion in an honest and fair election process. Starting from the nomination process to the results of the vote count won by one of the pairs of candidates who are considered defective by the community because they prioritize their political interests so that the other two pairs of candidates submit election result disputes to the Mahkamah Konstitusi to save Indonesian democracy. The purpose of researchers conducting research is to find out the role of the Mahkamah Konstitusi in resolving disputes over the 2024 presidential election. The research method used uses a qualitative approach by analyzing data from literature studies. The results showed that the Mahkamah Konstitusi rejected the dispute on the grounds that it was unfounded. In fact, there is a dissenting opinion that the application should be granted. This shows that the Mahkamah Konstitusi has lost its legitimacy as a legal protector and can also reduce public trust in legal institutions in Indonesia.